TESTES DE GERMINAÇÃO E VIGOR EM SEMENTES DE FEIJÃO IRRIGADO CULTIVAR BRS ESTILO, SAFRA 2023 - VILHARVA, Wellington Paulo Martinez; LOPES, Adriano da Silva; KRAESKI, Marcos Jefferson; FRANCO, Jhonatan da Silva (ANAIS DO ENIC, 2025)
-